Application of the Rapid Application Development (RAD) Method for Web-Based Financial Management and Wood Inventory Using CodeIgniter - Meyliana, Anastasia; Rapiyanta, Paulus Tofan; Andriani, Anik (ARRUS Journal of Engineering and Technology, 2024)
Financial management system and wood inventory at UD. Anugrah Limbah often faces problems that can affect operational efficiency and accuracy. Problems that arise include the fact that financial recording and wood inventory is still done manually, making it vulnerable to double recording, miscalculations or loss of data as well as other problems. This research discusses the application of the Rapid Application Development (RAD) method in developing financial and wood inventory management applications. The aim of this research is to design and implement an application that can increase efficiency and accuracy in managing finances and wood supplies at UD. Anugrah Limbah. The Rapid Application Development method was chosen because of its advantages in accelerating the application development process through an iterative and collaborative approach, which allows end users to actively participate in every stage of development. The research results show that by using the Rapid Application Development method, applications can be developed in a shorter time with quality maintained. The resulting application has features such as recording financial transactions, monitoring wood supplies, and reporting that is integrated and easy to access.